1997
DOI: 10.1007/s001200050135
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of metastases in patients with renal cell carcinoma

Abstract: The aim of the present study was to investigate the efficacy of surgical excision of metastases in patients with renal cell carcinoma (RCC). Eighteen patients with metastatic RCC underwent resection of metastases between 1988 and 1994 (pulmonary: n = 6; skeletal: n = 6; cerebral: n = 3; local relapse: n = 3). Two patients suffered from synchronous appearance of metastases, whereas in 16 cases a metachronous occurrence was observed. In 12 out of a total of 18 patients metastases were completely resected. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
0
2
1
Order By: Relevance
“…Patients with solitary lesions had a disease‐free survival that is comparable to patients presenting with several skeletal lesions. Studies have reported improved survival with wide resection of solitary osseous metastases with minimal or no local progression 25, 5, 7, 13, 26–30, whereas another study, like ours, found no effect on overall survival 31. The differences between these observations are likely related to patient selection bias and study design flaws inherent in retrospective studies.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Patients with solitary lesions had a disease‐free survival that is comparable to patients presenting with several skeletal lesions. Studies have reported improved survival with wide resection of solitary osseous metastases with minimal or no local progression 25, 5, 7, 13, 26–30, whereas another study, like ours, found no effect on overall survival 31. The differences between these observations are likely related to patient selection bias and study design flaws inherent in retrospective studies.…”
Section: Discussioncontrasting
confidence: 64%
“…Controversy remains concerning appropriate treatment of osseous metastatic renal cell carcinoma (Table III). Some studies have shown wide resection to be a positive prognostic indicator of improved survival 7; however, several others were unable to confirm these data 20, 5, 13. Some studies have demonstrated intralesional procedures have a high failure rate (5–40%) resulting in the need for further surgical interventions compared with patients undergoing wide resection 5, 21, 7, 22, 12, 23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation